Association Between Hair Diseases and COVID-19 Pandemic-Related Stress: A Cross-Sectional Study Analysis - Mahadi, Ashrafur Rahaman; Rafi, Md. Abdur; Shahriar, Tasnim; Seemanta, Senjuti; Rabbani, Md. Golam; Akter, Munjarin; Majumder, Mahabubul Islam; Hasan, M. Tasdik (Frontiers in Medicine, 2022)
Introduction: Psychological stress from ongoing COVID-19 pandemic potentially can aggravate the course of several stress-sensitive skin and hair diseases. The present study aimed to determine the potential association of COVID-19 stress with hair diseases like Telogen Effluvium (TE), Alopecia Areata (AA) and Seborrheic Dermatitis (SD) among medical students in Bangladesh. Method: This online-based cross-sectional study was conducted among 404 medical students of Bangladesh using a self-administered questionnaire including sociodemographic information, the status of hair diseases (TE, AA, SD), the COVID-19 fear scale, the IES-Covid-19, and the CSSQ scale to determine pandemic-related stress. Logistic regression model was used to analyze the association. Result: Overall prevalence of TE, AA and SD were 61.1%, 24.7% and 57.7% respectively with female predominance in case of TE and male predominance in case of AA and SD. More than half of the participants had Covid-19 related fear and traumatic stress symptoms. In multiple logistic regression model, smoking (aOR 2.93, 95% CI 1.29-6.65 for AA and aOR 4.19, 95% CI 1.83-9.56 for TE), Covid-19 related fear (aOR 1.70, 95% CI 1.01-2.89 for AA and aOR 2.620, 95% CI 1.25-5.48 for TE) and Covid-19 related